THE ROLE OF HUMAN THYMINE DNA GLYCOSYLASE IN EPIGENETIC REGULATION OF TRANSCRIPTION AND GENOME STABILITY (Experimental biology, 2023)
Thymine DNA glycosylase (TDG) attracted attention because of its ability to remove thymine, i.e., the normal DNA base, from G:T irregular pairs. This indicated its function in DNA base excision repair in the repair of G:C base pairs after deamination of 5-methylcytosine. Because of its apparent catalytic inefficiency, TDG was considered by some to be a poor DNA repair enzyme without an important biological function. However, it has been demonstrated that this enzyme can act as a key player in transcriptional regulation through interactions with various nuclear receptors and transcription factors, indicating its function in gene regulation, which appears to be crucial in developmental processes. Others have shown that TDG is involved in the epigenetic regulation of gene expression by protecting CpG-rich promoters from de novo DNA methylation and can initiate aberrant repair. Recent animal studies have revealed an association between loss of TDG and the onset of tumorigenesis. Thus, the purpose of this review is to bring together the results of various experiments in which thymine DNA-glycosylase has been studied since its discovery and to assess their implications for determining the possible physiological roles of this enzyme.
Keywords: Thymine DNA glycosylase, DNA repair, DNA demethylation, cancer